Perancangan Aplikasi E-Learning Berbasis Web pada SMA Negeri 1 Percut Sei Tuan dengan Metode Prototype - Muhammad Suwanda Ramadhani; Surya Hendra Putra (Politeknik Ganesha Medan, 2026)
This study aims to design and build a web-based e-learning application system at SMA Negeri 1 Percut Sei Tuan. Currently, the learning process is still carried out manually or through non-integrated media, which causes inefficiencies in managing materials, assignments, and student assessments. Therefore, this study developed an e-learning system to support more effective and structured online learning activities. This system allows teachers to upload materials, assign assignments, and conduct assessments digitally, while students can access materials, work on assignments, and receive feedback in real-time. This research was conducted through several stages, namely data collection, analysis of the current system, system design, prototype creation, user evaluation, and implementation. The method used is a prototype, which allows for gradual system development based on direct input from users. The results of the design show that the system built is able to support the online learning process and facilitate teachers and students in interacting digitally. With this system, it is hoped that the learning process at SMA Negeri 1 Percut Sei Tuan will be more efficient, transparent, and easy to monitor